2003
DOI: 10.1038/sj.jea.7500272
|View full text |Cite
|
Sign up to set email alerts
|

House dust and inorganic urinary arsenic in two Arizona mining towns

Abstract: Residents of copper mining and smelting towns may have increased risk of arsenic exposure from elevated arsenic contained in environmental media. To determine the relation of arsenic in house dust to inorganic urinary arsenic concentrations, a door-to-door survey was conducted in Hayden and Winkelman, Arizona. A total of 122 households (404 individuals) participated; 85 provided dust samples. Urine was collected at first morning void and analyzed for total and speciated arsenic. Speciation of arsenic was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Arsenic trioxide (ATO, As 2 O 3 ) is an important environmental dust that is a common contaminant around copper smelters (Milham and Strong, 1974, Hysong et al, 2003). Children living near copper smelters in Arizona were found to have elevated concentrations of arsenic in their urine, with an analysis of house dust containing ATO measured in excess of 300 μg/g (Morse, et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic trioxide (ATO, As 2 O 3 ) is an important environmental dust that is a common contaminant around copper smelters (Milham and Strong, 1974, Hysong et al, 2003). Children living near copper smelters in Arizona were found to have elevated concentrations of arsenic in their urine, with an analysis of house dust containing ATO measured in excess of 300 μg/g (Morse, et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Another study in the Arizona towns of Hayden and Winkelman, which are near an active copper smelter, did not find a significant relationship between house dust and inorganic arsenic in urine (Hysong et al, 2003). This study, however, was done primarily in adults, and it is possible that children in areas with higher soil and dust arsenic levels would also have higher inorganic-related arsenic exposures, as the Polissar study found.…”
Section: Discussionmentioning
confidence: 99%
“…These types of analyses, such as using soil sample concentrations to predict exposure and estimate health risks, are useful for risk assessment at specific sites ( Gress et al 2014 ). Also, some aggregate exposure modeling studies have used a multi-media, multi-pathway exposure assessment and identified house dust as an important source of exposure in mining communities ( Hysong et al 2003 ; O’Rourke et al 1999 ).To develop a stronger foundation of data for future modeling studies, workshop participant indicated that duplicate diet studies, more sampling of food and other media, and more speciation data in all exposure media are needed to develop a stronger foundation of data for future modeling studies.…”
Section: Exposure Assessments and Aggregate Exposuresmentioning
confidence: 99%